Checklists of Fish Species Infected with the Asian Tapeworm Schyzocotyle acheilognathi (Yamaguti, 1934) (Platyhelminthes: Cestoda) in Iraq - Mhaisen, Furhan (Iraqi Journal of Aquaculture, 2025)
Reviewing 112 references concerning the occurrence of the Asian tapeworm Schyzocotyle acheilognathi (Yamaguti, 1934) Brabec, Waeschenbach, Scholz, Littlewood & Kuchta, 2015, until the end of 2024, indicated that this cestode is known to infect 20 fish species in Iraq. Such records included three synonymous names of this cestode: Bothriocephalus acheilognathi, B. gowkongensis and B. opsariichthydis. In addition, five out of these 20 infected fish species were also reported to be infected with unspecified Schyzocotyle species (as Bothriocephalus species). The infected fishes were distributed in different water bodies in Iraq (rivers, lakes, marshes) as well as some fishponds, farms, one hatchery in seven provinces in addition to some fishes, obtained from fish markets in five provinces.